Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae) - Mayhé-Nunes, Antonio J.; Brandão, C. Roberto F. (Zootaxa, 2007)
We hereby revise the Jamaicensis group of species of Trachymyrmex (Myrmicinae: Attini), as the third part of our taxonomic revisionary studies on this fungus-growing ant genus. The species group we deal with here includes six taxa that share exclusively the antennal scrobes always reaching the posterior margin of the head and ending as two separate projections arising from the preocular and frontal carinae, giving the scrobe posterior region an “opened” appearance and an angular profile to the posterolateral corners, in frontal view. The Jamaicensis group is composed of Trachymyrmex atlanticus n. sp. (eastern Brazil), Trachymyrmex haytianus Wheeler & Mann, 1914 n. st. (Haiti, Jamaica), Trachymyrmex isthmicus Santschi, 1931 (Colombia, Ecuador, Panama), Trachymyrmex ixyodus n. sp. (northern Brazil, Suriname), Trachymyrmex jamaicensis (André, 1893) (Caribbean islands and southern USA), its synonyms (Trachymyrmex sharpii Forel, 1893; Trachymyrmex maritimus Wheeler, 1905 n. syn.; Trachymyrmex jamaicensis var. frontalis Santschi, 1925 n. syn., and Trachymyrmex jamaicensis cubaensis Wheeler, 1937 n. syn.), and Trachymyrmex zeteki Weber, 1940 (Colombia, Costa Rica, Ecuador, Panama). Trachymyrmex jamaicensis antiguensis Weber, 1938 is excluded from the Jamaicensis species group because it belongs to the Trachymyrmex Urichi species group. The only known Trachymyrmex fossil, T. primaevus Baroni Urbani, 1980, from the Dominican amber, does not belong to the Jamaicensis species group, as hypothesized earlier.